2008
DOI: 10.1111/j.1469-7610.2008.01952.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of ADHD, tics, and anxiety with dopamine transporter (DAT1) genotype in autism spectrum disorder

Abstract: Background Autism spectrum disorder (ASD) is associated with high rates of psychiatric disturbance to include attention-deficit/hyperactivity disorder (ADHD), tic disorder, and anxiety disorders. The aim of the present study was to examine the association between a variable number tandem repeat (VNTR) functional polymorphism located in the 3′-untranslated region of the dopamine transporter gene (DAT1) and the severity of these symptoms as well as the association between the DAT1 DdeI polymorphism and severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 50 publications
5
66
0
2
Order By: Relevance
“…29 Furthermore, it has been suggested that the 9-and 10-repeat alleles of the dopamine transporter may be associated with hyperactivity, impulsivity, social anxiety, and tic symptoms in autistic children. 30 In a PET study of autistic children, low levels of medial prefrontal dopaminergic activity were observed under anesthesia, 31 whereas increased dopamine D 2 receptor binding in the whole caudate and putamen has also been demonstrated. 32 These findings suggest that the alteration of both the serotonin and the dopamine systems is a feature of autism, although these findings remain equivocal and inconclusive.…”
Section: Arch Gen Psychiatry 2010;67(1):59-68mentioning
confidence: 99%
“…29 Furthermore, it has been suggested that the 9-and 10-repeat alleles of the dopamine transporter may be associated with hyperactivity, impulsivity, social anxiety, and tic symptoms in autistic children. 30 In a PET study of autistic children, low levels of medial prefrontal dopaminergic activity were observed under anesthesia, 31 whereas increased dopamine D 2 receptor binding in the whole caudate and putamen has also been demonstrated. 32 These findings suggest that the alteration of both the serotonin and the dopamine systems is a feature of autism, although these findings remain equivocal and inconclusive.…”
Section: Arch Gen Psychiatry 2010;67(1):59-68mentioning
confidence: 99%
“…A dopamine D1 receptor (DRD1) haplotype as well as DRD3 single-nucleotide polymorphisms have been associated with increased risk for ASD (Hettinger et al 2008;Staal 2014). Mutations in the dopamine transporter (DAT) have also been associated with ASD (Bowton et al 2014); DAT mutations that result in increased expression of the transporter, and thus likely lower synaptic levels of DA, are associated with increased social anxiety in ASD children (Gadow et al 2008). Together, these data suggest a deficit in social reward processing in ASD accompanied by genetic and functional abnormalities in the mesolimbic DA pathway.…”
Section: Social Cognition Versus Social Motivation Theories Of Autismmentioning
confidence: 99%
“…It is likely that other neurobiological anomalies co-occur, given the spectrum's extreme heterogeneity. Nonetheless, dopamine signaling anomalies have been associated with several ASD comorbidities, such as ADHD, anxiety, tics [45] , and executive function deficits [46] .…”
Section: Limitations Of the Dopamine Hypothesis Of Asdmentioning
confidence: 99%